Where'd you go, bernadette eaudiobook - Semple, Maria (2013)
A misanthropic matriarch leaves her eccentric family in crisis when she mysteriously disappears in this "whip-smart and divinely funny" novel that inspired the movie starring Cate Blanchett ( New York Times ). Bernadette Fox is notorious. To her Microsoft-guru husband, she's a fearlessly opinionated partner; to fellow private-school mothers in Seattle, she's a disgrace; to design mavens, she's a revolutionary architect; and to 15-year-old Bee, she is her best friend and, simply, Mom. Then Bernadette vanishes. It all began when Bee aced her report card and claimed her promised reward: a family trip to Antarctica. But Bernadette's intensifying allergy to Seattle — and people in general — has made her so agoraphobic that a virtual assistant in India now runs her most basic errands. A trip to the end of the earth is problematic. To find her mother, Bee compiles email messages, official documents, and secret correspondence — creating a compulsively readable and surprisingly touching novel about misplaced genius and a mother and daughter's role in an absurd world.